P16: CARDIAC ARREST AS A CONSEQUENCE OF AIR EMBOLISM STATUS POST CT-GUIDED LUNG BIOPSY. Issue 3 (23rd February 2016) - Pourmorteza, M; Murtaza, G; Mamdouhi, P; Ur Rahman, Z; Sethi, P; Paul, TK
Abstract : Purpose of Study: CT-guided transthoracic lung biopsy (CTLB) is a widely used procedure for the diagnosis of pulmonary lesions. Complication of air embolism has an incidence of 0.02%–0.06%. We report a fatal case of air embolism in the left atrium as a consequence of CTLB. Methods Used: A 82 years old white female who presented to the radiology department for further evaluation of a recently diagnosed right lung mass. Shortly following CTLB she became unresponsive and developed cardiopulmonary arrest. Cardio-pulmonary resuscitation (CPR) was performed according to ACLS guidelines. She was successfully resuscitation and admitted to the ICU.CT chest was performed immediately after resuscitation which showed frothy air dense material in the left atrium and one of the right pulmonary veins suggesting a Broncho venous fistula with air embolism. Patient was subsequently sent to hyperbaric oxygen chamber which she tolerated well. A repeat CT chest and head failed to depict any evidence of air embolism. She was successfully weaned from the mechanical ventilation and extubated the following day. Summary of Results: Air embolism following CTLB has a reported incidence of 0.02 to 0.06 but has catastrophic consequences if diagnosis is not made in a timely manner. The amount of air entry into the system is directly proportional to the severity of the patients symptoms. The mechanism of air entry in our patient was secondary to iatrogenic bronchovenous fistula. Conclusions: Despite such rarity and fatal complication, clinicians should be aware of systemic air embolus after lung biopsy and be ready to provide emergent management for the treatment of the patient.Abstract P16 Figure 1